Understanding the Detection of Shiga Toxin Producing Escherichia Coli: Virulence Factors, Pathogenicity Islands or Serotypes? - Colello, Rocío (2018)
Shiga toxin-producing Escherichia coli (STEC) are important food borne pathogens that can cause severe disease in children by producingtwo toxins (Stx1 and Stx2). This bacteria harbor several additional virulence factorsand have been classified in different serotypes that havebeen used as screening for detection of STEC. Aa is not possible to define when a STEC strain is pathogenic, it is important incorporate the riskassessment.